A kind of shadow blue glaze, ceramics having the glaze and preparation method thereof

By using specific formulas of the shadow blue glaze and adding fixed-effect flat adjustment and modified filler, the problem of difficult performance coordination of existing shadow blue glaze ceramic products is solved, and the ceramics are efficient antibacterial, gloss and wear resistance are achieved, and the acid and alkali resistance stability is improved.

CN119143478BActive Publication Date: 2025-02-28DEHUA COUNTRY HONG CERAMICS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411638041.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-16
Publication Date
2025-02-28
Estimated Expiration
2044-11-16

AI Technical Summary

Technical Problem

The existing shadow green glaze ceramic products have poor gloss performance, difficult to coordinately improve antibacterial properties, gloss and wear resistance, and have poor acid and alkali resistance stability, which reduces the efficiency of the product.

Method used

The specific formula of the shadow blue glaze is used, including potassium feldspar, quartz, calcium carbonate, zinc oxide, zirconium white frit and iron oxide, and the performance of the ceramic is improved by adding fixed-effect flat adjustment and modification filler agents.

Benefits of technology

It significantly coordinates and improves the antibacterial properties, gloss and wear resistance of ceramics, and improves the acid and alkali resistance of the product and improves the use efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of ceramics, and in particular to a shadow blue glaze, a ceramic having the glaze and a preparation method thereof, comprising the following steps: preparation of a ceramic body: weighing raw materials according to weight: 35-40 parts of sand, 15-20 parts of quartz, 3-5 parts of dolomite, 2-5 parts of bentonite, and 2-5 parts of kaolin. The ceramic having the shadow blue glaze of the present invention adopts a ceramic body and a shadow blue glaze to apply, and the antibacterial performance, glossiness and wear resistance of the ceramic product obtained by sintering improvement are coordinated and improved, and the acid and alkali resistance of the product is significantly stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a shadow blue glaze, a ceramic having the glaze and a preparation method thereof. Background Art

[0002] With the development of ceramic technology, more and more ceramic products are presented to the public. Compared with the more common pure-color ceramic glazes such as white porcelain and red porcelain, more and more consumers have begun to like different ceramic glaze styles, such as crackle glaze, retro glaze and blue-white glaze. Among them, blue-white glaze, also known as shadow blue glaze, has a glaze color between blue and white.

[0003] The ceramic products prepared with the existing shadow blue glaze have poor gloss performance. At the same time, the antibacterial performance, gloss and wear resistance of the products are difficult to improve in a coordinated manner. At the same time, the acid and alkali resistance of the products is poorly stable, which reduces the product's use efficiency. Based on this, the present invention further improves it. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a shadow blue glaze, a ceramic having the glaze and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a method for preparing a ceramic with a shadow green glaze, comprising the following steps:

[0007] Step 1: Preparation of ceramic body:

[0008] Weigh the raw materials according to weight: 35-40 parts of sand, 15-20 parts of quartz, 3-5 parts of dolomite, 2-5 parts of bentonite, and 2-5 parts of kaolin;

[0009] The raw materials are mixed and wet-milled at a speed of 1500 r / min for 1 hour to obtain a ball-milled material; the ball-milled material is pressed into a mold to obtain a ceramic body;

[0010] Step 2: Apply the shadow blue glaze to the ceramic body. After the application is completed, sintering is improved to obtain the ceramic with the shadow blue glaze.

[0011] Preferably, the pressing pressure is 10-15 MPa, and the pressing time is 20-30 min;

[0012] The application amount of shadow blue glaze is 550-560g / m 2 ;

[0013] The specific operation steps of the sintering improvement are: first sinter at a temperature of 550-570°C for 20-30 minutes, then heat up to 1250-1270°C at a rate of 2-5°C / min, sinter for 2 hours, and cool to room temperature after the sintering is completed.

[0014] The present invention provides a shadow green glaze, which is used in a method for preparing a ceramic having the shadow green glaze, and comprises the following raw materials in parts by weight:

[0015] 30-35 parts of potassium feldspar, 15-20 parts of quartz, 10-12 parts of calcium carbonate, 4-6 parts of zinc oxide, 15-16 parts of zirconium white frit, and 1-2 parts of iron oxide.

[0016] Preferably, the shadow blue glaze further comprises the following raw materials in parts by weight: 4-7 parts of a leveling agent and 3-5 parts of a modified filler;

[0017] The preparation method of the fixed-effect leveling agent is as follows:

[0018] S01: First, the nano-attapulgite is stirred and mixed in a sufficient amount of sulfuric acid solution, and then washed, filtered and dried to obtain dry nano-attapulgite;

[0019] The dried nano-attapulgite is thermally improved at 175-185° C. for 10-15 minutes, then heated to 350-360° C. at a rate of 2-5° C. / min, kept warm for 5 minutes, and finally air-cooled to room temperature to obtain thermally improved nano-attapulgite;

[0020] S02: Preparation of flat effect liquid:

[0021] Prepare a sodium lignin sulfonate solution with a mass fraction of 4-6%;

[0022] Blend 4-6 parts of barium carbonate, 2-5 parts of silane coupling agent KH560, and 1-3 parts of nano-silicon dioxide by weight, then add them to 6-10 parts of sodium lignin sulfonate solution, stir well, and obtain a flat effect liquid;

[0023] S03: soaking the heat-modified nano-attapulgite in a leveling liquid that is 5-8 times the total weight of the heat-modified nano-attapulgite, and after the soaking is completed, filtering and drying are performed to obtain a fixed-effect leveling agent.

[0024] Preferably, the immersion ultrasonic power of the immersion treatment is 450-470W, the immersion time is 20-30min, and the mass fraction of the sulfuric acid solution is 5%.

[0025] Preferably, the preparation method of the modified filler is:

[0026] S11: dissolving sodium alginate powder in 70° C. water in an amount of 5 times the total weight of the sodium alginate powder, then adding 5-8% of the total weight of sodium alginate powder sodium dodecylbenzene sulfonate solution and 3-6% of the total weight of the sodium alginate powder silane coupling agent KH560, and stirring evenly to obtain sodium alginate solution;

[0027] S12: adding the nano-alumina into a cerium nitrate solution which is 2-5 times the total weight of the nano-alumina and stirring the solution at a stirring speed of 550-650 r / min for 20 minutes, filtering and drying after the stirring is completed to obtain a cerium-doped nano-alumina agent;

[0028] S13: The cerium-doped nano-alumina agent, tourmaline additive and sodium alginate solution are mixed and ball-milled in a weight ratio of (2-4):2:(5-7) at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a modified filler.

[0029] Preferably, the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%; the mass fraction of the cerium nitrate solution is 4-6%.

[0030] Preferably, the preparation method of the tourmaline additive is:

[0031] The tourmaline is first stirred thoroughly in a 5% cobalt nitrate solution having a mass fraction of 3-5 times the total weight of the tourmaline, and then filtered and dried to obtain cobalt-doped tourmaline;

[0032] The cobalt-doped tourmaline and the modified liquid are subjected to ultrasonic modification treatment in a weight ratio of 2:5, the ultrasonic treatment is terminated, the treatment is filtered, and the tourmaline additive is obtained;

[0033] The modified liquid includes the following raw materials in parts by weight:

[0034] 5-8 parts of lanthanum chloride solution, 1-3 parts of glass fiber, 2-4 parts of nano calcium carbonate and 3-5 parts of triisopropoxy aluminum.

[0035] Preferably, the ultrasonic power of the ultrasonic modification treatment is 350-400W, the ultrasonic time is 20-30min; and the mass fraction of the lanthanum chloride solution is 3-5%.

[0036] The present invention also provides a ceramic with a shadow green glaze, which is prepared by the preparation method of the ceramic with a shadow green glaze.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The ceramic with shadow blue glaze of the present invention adopts ceramic body and shadow blue glaze to apply, and the antibacterial property, glossiness and wear resistance of the ceramic product obtained by sintering improvement are coordinated improved, and the acid and alkali resistance of the product is significantly stable;

[0039] The ceramic body is made of sand, quartz, dolomite, bentonite and kaolin. The strength and stability of the ceramic body obtained by matching the raw materials are good. The shadow blue glaze uses potassium feldspar, quartz, calcium carbonate, zinc oxide, zirconium white frit and iron oxide as the matrix material. By adding the fixed effect leveling agent and modified filler, the performance of the product is improved, the product performance balance and performance stability are optimized. The fixed effect leveling agent uses nano-attapulgite activated by acid solution, and then heat-modified at 175-185℃ for 10-15min, and then heated to 350-360℃ at a rate of 2-5℃ / min, kept warm for 5min, and finally air-conditioned. Cool to room temperature, and further optimize the activity of nano-attapulgite through segmented thermal improvement, so that the nano-attapulgite can be better immersed in the leveling liquid for improvement. The leveling liquid uses nano-silicon dioxide as the blending raw material through the co-coordination and co-assistance of the raw materials, and then cooperates with other raw materials in the leveling liquid to enhance the filling effect of the fixed-effect leveling agent in the system. The lamellar structure of nano-attapulgite and the spherical structure of nano-silicon dioxide can improve the coordination between the raw materials of the product, improve the antibacterial property and glossiness of the product system, and fill the system to improve the system's density and raw material connectivity, thereby coordinating and improving the product performance effect and optimizing the product performance effect;

[0040] The modified filler adopts sodium alginate powder which is dissolved in water, and then mixed with sodium dodecylbenzene sulfonate solution and silane coupling agent KH560. The interfacial activity of the matrix is ​​enhanced by the mixing between the raw materials, so that the cerium-doped nano-alumina agent and the tourmaline additive can be better adjusted and coordinated with each other. The cerium-doped nano-alumina agent is sent into the cerium nitrate solution through nano-alumina for stirring treatment, and the nano-alumina doped cerium body is optimized, so as to better improve the tourmaline additive. The tourmaline in the tourmaline additive is improved by cobalt nitrate solution and then modified with a modifying liquid. The glass fiber in the modifying liquid is mixed with raw materials such as nano-calcium carbonate, and the tourmaline modified by the modifying liquid is reinforced. The modified filler obtained has better reinforcing effect and leveling agent, so that the performance of the product is further improved. DETAILED DESCRIPTION

[0041] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] A method for preparing a ceramic with a shadow green glaze in this embodiment comprises the following steps:

[0043] Step 1: Preparation of ceramic body:

[0044] Weigh the raw materials according to weight: 35-40 parts of sand, 15-20 parts of quartz, 3-5 parts of dolomite, 2-5 parts of bentonite, and 2-5 parts of kaolin;

[0045] The raw materials are mixed and wet-milled at a speed of 1500 r / min for 1 hour to obtain a ball-milled material; the ball-milled material is pressed into a mold to obtain a ceramic body;

[0046] Step 2: Apply the shadow blue glaze to the ceramic body. After the application is completed, sintering is improved to obtain the ceramic with the shadow blue glaze.

[0047] The pressing pressure of this embodiment is 10-15MPa, and the pressing time is 20-30min;

[0048] The application amount of shadow blue glaze is 550-560g / m 2 ;

[0049] The specific operation steps of the sintering improvement are: first sinter at a temperature of 550-570°C for 20-30 minutes, then heat up to 1250-1270°C at a rate of 2-5°C / min, sinter for 2 hours, and cool to room temperature after the sintering is completed.

[0050] A shadow green glaze of this embodiment is used in the preparation method of the ceramic with shadow green glaze, comprising the following raw materials in parts by weight:

[0051] 30-35 parts of potassium feldspar, 15-20 parts of quartz, 10-12 parts of calcium carbonate, 4-6 parts of zinc oxide, 15-16 parts of zirconium white frit, and 1-2 parts of iron oxide.

[0052] When preparing the shadow green glaze of this embodiment, the raw materials in the shadow green glaze are blended and wet-milled to obtain the shadow green glaze, with a ball milling speed of 1500 r / min and a ball milling time of 1 hour.

[0053] The shadow green glaze of this embodiment may also include the following raw materials in parts by weight: 4-7 parts of a leveling agent, 3-5 parts of a modified filler;

[0054] The preparation method of the fixed-effect leveling agent is as follows:

[0055] S01: First, the nano-attapulgite is stirred and mixed in a sufficient amount of sulfuric acid solution, and then washed, filtered and dried to obtain dry nano-attapulgite;

[0056] The dried nano-attapulgite is thermally improved at 175-185° C. for 10-15 minutes, then heated to 350-360° C. at a rate of 2-5° C. / min, kept warm for 5 minutes, and finally air-cooled to room temperature to obtain thermally improved nano-attapulgite;

[0057] S02: Preparation of flat effect liquid:

[0058] Prepare a sodium lignin sulfonate solution with a mass fraction of 4-6%;

[0059] Blend 4-6 parts of barium carbonate, 2-5 parts of silane coupling agent KH560, and 1-3 parts of nano-silicon dioxide by weight, then add them to 6-10 parts of sodium lignin sulfonate solution, stir well, and obtain a flat effect liquid;

[0060] S03: soaking the heat-modified nano-attapulgite in a leveling liquid that is 5-8 times the total weight of the heat-modified nano-attapulgite, and after the soaking is completed, filtering and drying are performed to obtain a fixed-effect leveling agent.

[0061] The immersion ultrasonic power of the immersion treatment in this embodiment is 450-470W, the immersion time is 20-30min, and the mass fraction of the sulfuric acid solution is 5%.

[0062] The preparation method of the modified filler of this embodiment is:

[0063] S11: dissolving sodium alginate powder in 70° C. water in an amount of 5 times the total weight of the sodium alginate powder, then adding 5-8% of the total weight of sodium alginate powder sodium dodecylbenzene sulfonate solution and 3-6% of the total weight of the sodium alginate powder silane coupling agent KH560, and stirring evenly to obtain sodium alginate solution;

[0064] S12: adding the nano-alumina into a cerium nitrate solution which is 2-5 times the total weight of the nano-alumina and stirring the solution at a stirring speed of 550-650 r / min for 20 minutes, filtering and drying after the stirring is completed to obtain a cerium-doped nano-alumina agent;

[0065] S13: The cerium-doped nano-alumina agent, tourmaline additive and sodium alginate solution are mixed and ball-milled in a weight ratio of (2-4):2:(5-7) at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a modified filler.

[0066] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 2-5%; the mass fraction of the cerium nitrate solution is 4-6%.

[0067] The preparation method of the tourmaline additive of the present embodiment is:

[0068] The tourmaline is first stirred thoroughly in a 5% cobalt nitrate solution having a mass fraction of 3-5 times the total weight of the tourmaline, and then filtered and dried to obtain cobalt-doped tourmaline;

[0069] The cobalt-doped tourmaline and the modified liquid are subjected to ultrasonic modification treatment in a weight ratio of 2:5, the ultrasonic treatment is terminated, the treatment is filtered, and the tourmaline additive is obtained;

[0070] The modified liquid includes the following raw materials in parts by weight:

[0071] 5-8 parts of lanthanum chloride solution, 1-3 parts of glass fiber, 2-4 parts of nano calcium carbonate and 3-5 parts of triisopropoxy aluminum.

[0072] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 350-400W, the ultrasonic time is 20-30min, and the mass fraction of the lanthanum chloride solution is 3-5%.

[0073] The ceramic with shadow green glaze of the present embodiment is made by the preparation method of the ceramic with shadow green glaze mentioned above.

[0074] Example 1: A method for preparing a ceramic having a green glaze, comprising the following steps:

[0075] Step 1: Preparation of ceramic body:

[0076] Weigh the raw materials according to weight: 35 parts of sand, 15 parts of quartz, 3 parts of dolomite, 2 parts of bentonite, and 2 parts of kaolin;

[0077] The raw materials are mixed and wet-milled at a speed of 1500 r / min for 1 hour to obtain a ball-milled material; the ball-milled material is pressed into a mold to obtain a ceramic body;

[0078] Step 2: Apply the shadow blue glaze to the ceramic body. After the application is completed, sintering is improved to obtain the ceramic with the shadow blue glaze.

[0079] The pressing pressure of this embodiment is 10MPa and the pressing time is 20min;

[0080] The amount of Yingqing glaze applied is 550g / m 2 ;

[0081] The specific operation steps of the sintering improvement are: first sinter at 550°C for 20 minutes, then heat to 1250°C at a rate of 2°C / min, sinter for 2 hours, and cool to room temperature after sintering.

[0082] A shadow green glaze of this embodiment is used in the preparation method of the ceramic with shadow green glaze, comprising the following raw materials in parts by weight:

[0083] 30 parts of potassium feldspar, 15 parts of quartz, 10 parts of calcium carbonate, 4 parts of zinc oxide, 15 parts of zirconium white frit, 1 part of iron oxide, 4 parts of fixed effect leveling agent, and 3 parts of modified filler.

[0084] When preparing the shadow green glaze of this embodiment, the raw materials in the shadow green glaze are blended and wet-milled to obtain the shadow green glaze, with a ball milling speed of 1500 r / min and a ball milling time of 1 hour.

[0085] The preparation method of the fixed-effect leveling agent is as follows:

[0086] S01: First, the nano-attapulgite is stirred and mixed in a sufficient amount of sulfuric acid solution, and then washed, filtered and dried to obtain dry nano-attapulgite;

[0087] The dried nano-attapulgite was thermally improved at 175°C for 10 minutes, then heated to 350°C at a rate of 2°C / min, kept at that temperature for 5 minutes, and finally air-cooled to room temperature to obtain thermally improved nano-attapulgite.

[0088] S02: Preparation of flat effect liquid:

[0089] Prepare a 4% sodium lignin sulfonate solution;

[0090] Blend 4 parts of barium carbonate, 2 parts of silane coupling agent KH560, and 1 part of nano-silicon dioxide by weight, then add them to 6 parts of sodium lignin sulfonate solution, stir well, and obtain a flat effect liquid;

[0091] S03: soaking the heat-modified nano-attapulgite in a leveling liquid that is 5-8 times the total weight of the heat-modified nano-attapulgite, and after the soaking is completed, filtering and drying are performed to obtain a fixed-effect leveling agent.

[0092] The immersion ultrasonic power of the immersion treatment in this embodiment is 450W, the immersion time is 20min, and the mass fraction of the sulfuric acid solution is 5%.

[0093] The preparation method of the modified filler of this embodiment is:

[0094] S11: dissolving sodium alginate powder in 70°C water in an amount of 5 times the total weight of the sodium alginate powder, then adding 5% sodium dodecylbenzene sulfonate solution in an amount of 5% of the total weight of the sodium alginate powder and 3% silane coupling agent KH560 in an amount of 3% of the total weight of the sodium alginate powder, and stirring evenly to obtain a sodium alginate solution;

[0095] S12: adding the nano-alumina into a cerium nitrate solution twice the total weight of the nano-alumina and stirring the solution at a stirring speed of 550 r / min for 20 minutes. After the stirring is completed, the solution is filtered and dried to obtain a cerium-doped nano-alumina agent;

[0096] S13: The cerium-doped nano-alumina agent, the tourmaline additive and the sodium alginate solution are mixed and ball-milled in a weight ratio of 2:2:5 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a modified filler.

[0097] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 2%; the mass fraction of the cerium nitrate solution is 4%.

[0098] The preparation method of the tourmaline additive of the present embodiment is:

[0099] The tourmaline is firstly stirred in a 5% cobalt nitrate solution with a mass fraction of 3 times the total weight of the tourmaline, and then filtered and dried to obtain cobalt-doped tourmaline;

[0100] The cobalt-doped tourmaline and the modified liquid are subjected to ultrasonic modification treatment in a weight ratio of 2:5, the ultrasonic treatment is terminated, the treatment is filtered, and the tourmaline additive is obtained;

[0101] The modified liquid includes the following raw materials in parts by weight:

[0102] 5 parts of lanthanum chloride solution, 1 part of glass fiber, 2 parts of nano calcium carbonate and 3 parts of triisopropoxy aluminum.

[0103] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 350W, and the ultrasonic time is 20min; the mass fraction of the lanthanum chloride solution is 3%.

[0104] The ceramic with shadow green glaze of the present embodiment is made by the preparation method of the ceramic with shadow green glaze mentioned above.

[0105] Example 2: A method for preparing a ceramic having a green glaze, comprising the following steps:

[0106] Step 1: Preparation of ceramic body:

[0107] Weigh the raw materials according to weight: 40 parts of sand, 20 parts of quartz, 5 parts of dolomite, 5 parts of bentonite, and 5 parts of kaolin;

[0108] The raw materials are mixed and wet-milled at a speed of 1500 r / min for 1 hour to obtain a ball-milled material; the ball-milled material is pressed into a mold to obtain a ceramic body;

[0109] Step 2: Apply the shadow blue glaze to the ceramic body. After the application is completed, sintering is improved to obtain the ceramic with the shadow blue glaze.

[0110] The pressing pressure of this embodiment is 15MPa and the pressing time is 30min;

[0111] The amount of Yingqing glaze applied is 560g / m 2 ;

[0112] The specific operation steps of sintering improvement are: first sinter at 570°C for 30 minutes, then heat to 1270°C at a rate of 5°C / min, sinter for 2 hours, and cool to room temperature after sintering.

[0113] A shadow green glaze of this embodiment is used in the preparation method of the ceramic with shadow green glaze, comprising the following raw materials in parts by weight:

[0114] 35 parts of potassium feldspar, 20 parts of quartz, 12 parts of calcium carbonate, 6 parts of zinc oxide, 16 parts of zirconium white frit, 2 parts of iron oxide, 7 parts of leveling agent, and 5 parts of modified filler.

[0115] When preparing the shadow green glaze of this embodiment, the raw materials in the shadow green glaze are blended and wet-milled to obtain the shadow green glaze, with a ball milling speed of 1500 r / min and a ball milling time of 1 hour.

[0116] The preparation method of the fixed-effect leveling agent is as follows:

[0117] S01: First, the nano-attapulgite is stirred and mixed in a sufficient amount of sulfuric acid solution, and then washed, filtered and dried to obtain dry nano-attapulgite;

[0118] The dried nano-attapulgite was thermally improved at 185°C for 15 minutes, then heated to 360°C at a rate of 5°C / min, kept at that temperature for 5 minutes, and finally air-cooled to room temperature to obtain thermally improved nano-attapulgite.

[0119] S02: Preparation of flat effect liquid:

[0120] Prepare a 6% sodium lignin sulfonate solution;

[0121] By weight, 6 parts of barium carbonate, 5 parts of silane coupling agent KH560, and 3 parts of nano-silicon dioxide are mixed, and then added into 10 parts of sodium lignin sulfonate solution, and stirred sufficiently to obtain a flat effect liquid;

[0122] S03: The heat-modified nano-attapulgite is immersed in a leveling liquid of 8 times the total weight of the heat-modified nano-attapulgite. After the immersion is completed, the liquid is filtered and dried to obtain a fixed-effect leveling agent.

[0123] The immersion ultrasonic power of the immersion treatment in this embodiment is 470W, the immersion time is 30min, and the mass fraction of the sulfuric acid solution is 5%.

[0124] The preparation method of the modified filler of this embodiment is:

[0125] S11: dissolving sodium alginate powder in 70°C water in an amount of 5 times the total weight of the sodium alginate powder, then adding 8% of the total weight of sodium alginate powder sodium dodecylbenzene sulfonate solution and 6% of the total weight of sodium alginate powder silane coupling agent KH560, stirring evenly to obtain sodium alginate solution;

[0126] S12: adding the nano-alumina into a cerium nitrate solution with a weight 5 times that of the total weight of the nano-alumina and stirring the solution at a stirring speed of 650 r / min for 20 minutes, filtering and drying after the stirring is completed to obtain a cerium-doped nano-alumina agent;

[0127] S13: The cerium-doped nano-alumina agent, the tourmaline additive and the sodium alginate solution are mixed and ball-milled in a weight ratio of 4:2:7 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a modified filler.

[0128] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 5%; the mass fraction of the cerium nitrate solution is 6%.

[0129] The preparation method of the tourmaline additive of the present embodiment is:

[0130] The tourmaline is firstly stirred in a 5% cobalt nitrate solution with a mass fraction of 5 times the total weight of the tourmaline, and then filtered and dried to obtain cobalt-doped tourmaline;

[0131] The cobalt-doped tourmaline and the modified liquid are subjected to ultrasonic modification treatment in a weight ratio of 2:5, the ultrasonic treatment is terminated, the treatment is filtered, and the tourmaline additive is obtained;

[0132] The modified liquid includes the following raw materials in parts by weight:

[0133] 8 parts of lanthanum chloride solution, 3 parts of glass fiber, 4 parts of nano calcium carbonate and 5 parts of triisopropoxy aluminum.

[0134] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 400 W, and the ultrasonic time is 30 min; the mass fraction of the lanthanum chloride solution is 5%.

[0135] The ceramic with shadow green glaze of the present embodiment is made by the preparation method of the ceramic with shadow green glaze mentioned above.

[0136] Embodiment 3: A method for preparing a ceramic having a green glaze, comprising the following steps:

[0137] Step 1: Preparation of ceramic body:

[0138] Weigh the raw materials according to weight: 37.5 parts of sand, 17.5 parts of quartz, 4 parts of dolomite, 3.5 parts of bentonite, and 3.5 parts of kaolin;

[0139] The raw materials are mixed and wet-milled at a speed of 1500 r / min for 1 hour to obtain a ball-milled material; the ball-milled material is pressed into a mold to obtain a ceramic body;

[0140] Step 2: Apply the shadow blue glaze to the ceramic body. After the application is completed, sintering is improved to obtain the ceramic with the shadow blue glaze.

[0141] The pressing pressure of this embodiment is 12.5MPa, and the pressing time is 25min;

[0142] The amount of Yingqing glaze applied is 570g / m 2;

[0143] The specific operation steps of sintering improvement are: first sinter at 565°C for 25 minutes, then heat to 1260°C at a rate of 3.5°C / min, sinter for 2 hours, and cool to room temperature after sintering.

[0144] A shadow green glaze of this embodiment is used in the preparation method of the ceramic with shadow green glaze, comprising the following raw materials in parts by weight:

[0145] 32.5 parts of potassium feldspar, 17.5 parts of quartz, 11 parts of calcium carbonate, 5 parts of zinc oxide, 15.5 parts of zirconium white frit, 1.5 parts of iron oxide, 5.5 parts of leveling agent, and 4 parts of modified filler.

[0146] When preparing the shadow green glaze of this embodiment, the raw materials in the shadow green glaze are blended and wet-milled to obtain the shadow green glaze, with a ball milling speed of 1500 r / min and a ball milling time of 1 hour.

[0147] The preparation method of the fixed-effect leveling agent is as follows:

[0148] S01: First, the nano-attapulgite is stirred and mixed in a sufficient amount of sulfuric acid solution, and then washed, filtered and dried to obtain dry nano-attapulgite;

[0149] The dried nano-attapulgite was thermally improved at 180°C for 12.5 min, then heated to 355°C at a rate of 3.5°C / min, kept at that temperature for 5 min, and finally air-cooled to room temperature to obtain thermally improved nano-attapulgite.

[0150] S02: Preparation of flat effect liquid:

[0151] Prepare a 5% sodium lignin sulfonate solution;

[0152] By weight, 5 parts of barium carbonate, 3.5 parts of silane coupling agent KH560, and 2 parts of nano-silicon dioxide are mixed, and then added into 8 parts of sodium lignin sulfonate solution, and stirred sufficiently to obtain a flat effect liquid;

[0153] S03: The heat-modified nano-attapulgite is immersed in a leveling liquid which is 6.5 times of the total weight of the heat-modified nano-attapulgite. After the immersion is completed, the liquid is filtered and dried to obtain a fixed-effect leveling agent.

[0154] The immersion ultrasonic power of the immersion treatment in this embodiment is 460W, the immersion time is 25min, and the mass fraction of the sulfuric acid solution is 5%.

[0155] The preparation method of the modified filler of this embodiment is:

[0156] S11: dissolving sodium alginate powder in 70°C water in an amount of 5 times the total weight of the sodium alginate powder, then adding 6.5% of the total weight of sodium alginate powder sodium dodecylbenzene sulfonate solution and 4.5% of the total weight of the sodium alginate powder silane coupling agent KH560, and stirring evenly to obtain sodium alginate solution;

[0157] S12: adding the nano-alumina into a cerium nitrate solution with a weight of 3.5 times the total weight of the nano-alumina and stirring the solution at a stirring speed of 600 r / min for 20 minutes. After the stirring is completed, the solution is filtered and dried to obtain a cerium-doped nano-alumina agent;

[0158] S13: The cerium-doped nano-alumina agent, the tourmaline additive and the sodium alginate solution are mixed and ball-milled in a weight ratio of 3:2:6 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a modified filler.

[0159] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 3.5%; the mass fraction of the cerium nitrate solution is 5%.

[0160] The preparation method of the tourmaline additive of the present embodiment is:

[0161] The tourmaline is firstly stirred in a 5% cobalt nitrate solution with a mass fraction of 4 times the total weight of the tourmaline, and then filtered and dried to obtain cobalt-doped tourmaline;

[0162] The cobalt-doped tourmaline and the modified liquid are subjected to ultrasonic modification treatment in a weight ratio of 2:5, the ultrasonic treatment is terminated, the treatment is filtered, and the tourmaline additive is obtained;

[0163] The modified liquid includes the following raw materials in parts by weight:

[0164] 6.5 parts of lanthanum chloride solution, 2 parts of glass fiber, 3 parts of nano calcium carbonate and 4 parts of triisopropoxy aluminum.

[0165] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 370W, and the ultrasonic time is 25min; the mass fraction of the lanthanum chloride solution is 4%.

[0166] The ceramic with shadow green glaze of the present embodiment is made by the preparation method of the ceramic with shadow green glaze mentioned above.

[0167] Comparative Example 1:

[0168] The difference from Example 3 is that no leveling agent is added to the shadow blue glaze.

[0169] Comparative Example 2:

[0170] The difference from Example 3 is that the thermally improved nano attapulgite is replaced by nano attapulgite in the preparation of the fixed-effect leveling agent.

[0171] Comparative Example 3:

[0172] The difference from Example 3 is that no flat-effect liquid treatment was used.

[0173] Comparative Example 4:

[0174] The difference from Example 3 is that barium carbonate and silane coupling agent KH560 are not added in the preparation of the flat-effect liquid.

[0175] Comparative Example 5:

[0176] The difference from Example 3 is that no nano-silicon dioxide is added in the preparation of the flat-effect liquid, and deionized water is used instead of the sodium lignin sulfonate solution.

[0177] Comparative Example 6:

[0178] The difference from Example 3 is that no modified filler is added.

[0179] Comparative Example 7:

[0180] The difference from Example 3 is that no cerium-doped nano-alumina agent is added in the preparation of the modified filler.

[0181] Comparative Example 8:

[0182] The difference from Example 3 is that the cerium-doped nano-alumina agent is replaced by nano-alumina.

[0183] Comparative Example 9:

[0184] The difference from Example 3 is that the sodium alginate solution is replaced by a sodium alginate solution with a mass fraction of 5%.

[0185] Comparative Example 10:

[0186] The difference from Example 3 is that no tourmaline additive is added in the preparation of the modified filler.

[0187] The performance of the ceramic products of Examples 1 to 3 and Comparative Examples 1 to 10 was tested. The products were placed in 2% hydrochloric acid mist for 12 hours and then in 5% sodium hydroxide alkaline mist for 12 hours. The above was one cycle. The cycle test was repeated 10 times. The test results are shown in Table 1.

[0188] Table 1 Performance test results of ceramic products of Examples 1 to 3 and Comparative Examples 1 to 10:

[0189]

[0190] From Examples 1-3 and Comparative Examples 1-10, it can be seen that the product in Example 3 has excellent antibacterial properties, glossiness and wear resistance, and the acid and alkali stability of the product is significant, and the performance of the product can achieve coordinated improvement;

[0191] From Comparative Example 1, Comparative Example 6 and Example 3, it can be seen that the shadow blue glaze does not add a fixed effect leveling agent and a modified filler, and the performance effect of the product deteriorates significantly, especially under acid and alkali resistance conditions, the performance stability of the product deteriorates more significantly. The present invention adopts a fixed effect leveling agent and a modified filler to cooperate with each other, and the product performance effect is significant;

[0192] From Comparative Examples 2-5 and Example 3, it can be seen that the thermally improved nano attapulgite in the preparation of the fixed-effect leveling agent is replaced by nano attapulgite, no leveling liquid treatment is used, barium carbonate and silane coupling agent KH560 are not added in the preparation of the leveling liquid, nano silicon dioxide is not added in the preparation of the leveling liquid, and deionized water is used instead of the sodium lignin sulfonate solution, and the performance of the product tends to deteriorate;

[0193] The fixed-effect leveling agent obtained by combining the leveling liquid obtained by the specific method of the present invention with the heat-modified nano-attapulgite has the most significant product performance effect. The effect of using other methods instead is not as obvious as that of the present invention.

[0194] It can be seen from Comparative Examples 7-10 and Example 3 that the performance of the products tended to deteriorate when no cerium-doped nano-alumina agent was added in the preparation of the modified filler, when the cerium-doped nano-alumina agent was replaced by nano-alumina, when the sodium alginate solution was replaced by a 5% by mass sodium alginate solution, and when no tourmaline additive was added in the preparation of the modified filler. In particular, when no tourmaline additive was added in the preparation of the modified filler, the performance of the product deteriorated more significantly. At the same time, the performance of the modified filler obtained by the specific process of using the cerium-doped nano-alumina agent obtained by the specific method of the present invention in combination with sodium alginate solution and tourmaline additives was the most significant.

[0195] The present invention further explores the product performance through the preparation of tourmaline additives.

[0196] Experimental Example 1:

[0197] The only difference from Example 3 is that no modifying liquid treatment is used in the preparation of the tourmaline additive.

[0198] Experimental Example 2:

[0199] The only difference from Example 3 is that the cobalt nitrate solution treatment was not used in the preparation of the tourmaline additive.

[0200] Experimental Example 3:

[0201] The only difference from Example 3 is that no glass fiber is added to the modified liquid.

[0202] Experimental Example 4:

[0203] The only difference from Example 3 is that no nano calcium carbonate is added to the modified solution.

[0204] Experimental Example 5:

[0205] The only difference from Example 3 is that no triisopropoxyaluminum is added to the modified liquid.

[0206] Experimental Example 6:

[0207] The only difference from Example 3 is that the lanthanum chloride solution is replaced by water.

[0208] The performance of the ceramic products of Experimental Examples 1 to 6 was tested. The products were placed in 2% hydrochloric acid mist for 12 hours and then in 5% sodium hydroxide alkaline mist for 12 hours. The above was one cycle. The cycle test was repeated 10 times. The test results are shown in Table 2.

[0209] Table 2 Performance test results of ceramic products of Experimental Examples 1 to 6:

[0210]

[0211] It can be seen from Experimental Examples 1-6 that the performance of the product changes when the modifying liquid is not used for the preparation of the tourmaline additive. In the preparation of the tourmaline additive, the performance deterioration is most obvious. When glass fiber is not added to the modifying liquid, nano-calcium carbonate is not added to the modifying liquid, triisopropoxyaluminum is not added to the modifying liquid, and water is used instead of lanthanum chloride solution, the performance of the product has a tendency to deteriorate to varying degrees. The modifying liquid is obtained by the specific method of the present invention, and the product performance effect is most obvious. At the same time, cobalt nitrate solution is not used for the preparation of the tourmaline additive, and the performance of the product also shows a tendency to deteriorate. The preparation of the tourmaline additive using other methods instead of the tourmaline additive is not as significant as the effect of the present invention. The preparation of the tourmaline additive of the present invention is unique.

[0212] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0213] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing ceramics with shadow blue glaze, characterized in that: The following steps are involved: Step 1: Preparation of ceramic body: Weigh the raw materials according to weight: 35-40 parts of sand, 15-20 parts of quartz, 3-5 parts of dolomite, 2-5 parts of bentonite, and 2-5 parts of kaolin; The raw materials are mixed and wet-milled at a speed of 1500 r / min for 1 hour to obtain a ball-milled material; the ball-milled material is pressed into a mold to obtain a ceramic body; Step 2: applying the shadow blue glaze to the ceramic body, and after the application is completed, sintering is improved to obtain the ceramic with the shadow blue glaze; The shadow blue glaze comprises the following raw materials in parts by weight: Potassium feldspar 30-35 parts, quartz 15-20 parts, calcium carbonate 10-12 parts, zinc oxide 4-6 parts, zirconium white frit 15-16 parts, iron oxide 1-2 parts, fixed effect leveling agent 4-7 parts, modified filler 3-5 parts; The preparation method of the fixed-effect leveling agent is as follows: S01: First, the nano-attapulgite is stirred and mixed in a sufficient amount of sulfuric acid solution, and then washed with water, filtered and dried to obtain dry nano-attapulgite; The dried nano-attapulgite is thermally improved at 175-185° C. for 10-15 minutes, then heated to 350-360° C. at a rate of 2-5° C. / min, kept warm for 5 minutes, and finally air-cooled to room temperature to obtain thermally improved nano-attapulgite; S02: Preparation of flat effect liquid: Prepare a sodium lignin sulfonate solution with a mass fraction of 4-6%; Blend 4-6 parts of barium carbonate, 2-5 parts of silane coupling agent KH560, and 1-3 parts of nano-silicon dioxide by weight, then add them to 6-10 parts of sodium lignin sulfonate solution, stir well, and obtain a flat effect liquid; S03: soaking the heat-modified nano-attapulgite in a leveling liquid that is 5-8 times the total weight of the heat-modified nano-attapulgite, and after the soaking is completed, filtering and drying to obtain a fixed-effect leveling agent; The preparation method of the modified filler is: S11: dissolving sodium alginate powder in 70° C. water in an amount of 5 times the total weight of the sodium alginate powder, then adding 5-8% of the total weight of sodium alginate powder sodium dodecylbenzene sulfonate solution and 3-6% of the total weight of the sodium alginate powder silane coupling agent KH560, and stirring evenly to obtain sodium alginate solution; S12: adding the nano-alumina into a cerium nitrate solution which is 2-5 times the total weight of the nano-alumina and stirring the solution at a stirring speed of 550-650 r / min for 20 minutes, filtering and drying after the stirring is completed to obtain a cerium-doped nano-alumina agent; S13: mixing the cerium-doped nano-alumina agent, the tourmaline additive and the sodium alginate solution in a weight ratio of (2-4):2:(5-7) and subjecting them to ball milling treatment at a ball milling speed of 1500 r / min for 2 h. After the ball milling is completed, washing, filtering and drying are performed to obtain a modified filler; The preparation method of the tourmaline additive is: The tourmaline is firstly stirred in a 5% cobalt nitrate solution with a mass fraction of 3-5 times the total weight of the tourmaline, and then filtered and dried to obtain cobalt-doped tourmaline; The cobalt-doped tourmaline and the modified liquid are subjected to ultrasonic modification treatment in a weight ratio of 2:5, the ultrasonic treatment is terminated, the treatment is filtered, and the tourmaline additive is obtained; The modified liquid includes the following raw materials in parts by weight: 5-8 parts of lanthanum chloride solution, 1-3 parts of glass fiber, 2-4 parts of nano calcium carbonate and 3-5 parts of triisopropoxy aluminum.

2. The method for preparing a ceramic with a shadow green glaze according to claim 1, characterized in that: The pressing pressure is 10-15 MPa, and the pressing time is 20-30 min; The application amount of shadow blue glaze is 550-560g / m 2 ; The specific operation steps of the sintering improvement are: first sinter at a temperature of 550-570°C for 20-30 minutes, then heat up to 1250-1270°C at a rate of 2-5°C / min, sinter for 2 hours, and cool to room temperature after the sintering is completed.

3. A shadow blue glaze, used in the method for preparing a ceramic having a shadow blue glaze as claimed in any one of claims 1 to 2, characterized in that: It includes the following raw materials in parts by weight: Potassium feldspar 30-35 parts, quartz 15-20 parts, calcium carbonate 10-12 parts, zinc oxide 4-6 parts, zirconium white frit 15-16 parts, iron oxide 1-2 parts, fixed effect leveling agent 4-7 parts, modified filler 3-5 parts; The preparation method of the fixed-effect leveling agent is as follows: S01: First, the nano-attapulgite is stirred and mixed in a sufficient amount of sulfuric acid solution, and then washed with water, filtered and dried to obtain dry nano-attapulgite; The dried nano-attapulgite is thermally improved at 175-185° C. for 10-15 minutes, then heated to 350-360° C. at a rate of 2-5° C. / min, kept warm for 5 minutes, and finally air-cooled to room temperature to obtain thermally improved nano-attapulgite; S02: Preparation of flat effect liquid: Prepare a sodium lignin sulfonate solution with a mass fraction of 4-6%; Blend 4-6 parts of barium carbonate, 2-5 parts of silane coupling agent KH560, and 1-3 parts of nano-silicon dioxide by weight, then add them to 6-10 parts of sodium lignin sulfonate solution, stir well, and obtain a flat effect liquid; S03: soaking the heat-modified nano-attapulgite in a leveling liquid that is 5-8 times the total weight of the heat-modified nano-attapulgite, and after the soaking is completed, filtering and drying to obtain a fixed-effect leveling agent; The preparation method of the modified filler is: S11: dissolving sodium alginate powder in 70° C. water in an amount of 5 times the total weight of the sodium alginate powder, then adding 5-8% of the total weight of sodium alginate powder sodium dodecylbenzene sulfonate solution and 3-6% of the total weight of the sodium alginate powder silane coupling agent KH560, and stirring evenly to obtain sodium alginate solution; S12: adding the nano-alumina into a cerium nitrate solution which is 2-5 times the total weight of the nano-alumina and stirring the solution at a stirring speed of 550-650 r / min for 20 minutes, filtering and drying after the stirring is completed to obtain a cerium-doped nano-alumina agent; S13: mixing the cerium-doped nano-alumina agent, the tourmaline additive and the sodium alginate solution in a weight ratio of (2-4):2:(5-7) and subjecting them to ball milling treatment at a ball milling speed of 1500 r / min for 2 h. After the ball milling is completed, washing, filtering and drying are performed to obtain a modified filler; The preparation method of the tourmaline additive is: The tourmaline is firstly stirred in a 5% cobalt nitrate solution with a mass fraction of 3-5 times the total weight of the tourmaline, and then filtered and dried to obtain cobalt-doped tourmaline; The cobalt-doped tourmaline and the modified liquid are subjected to ultrasonic modification treatment in a weight ratio of 2:5, the ultrasonic treatment is terminated, the treatment is filtered, and the tourmaline additive is obtained; The modified liquid includes the following raw materials in parts by weight: 5-8 parts of lanthanum chloride solution, 1-3 parts of glass fiber, 2-4 parts of nano calcium carbonate and 3-5 parts of triisopropoxy aluminum.

4. The shadow blue glaze according to claim 3, characterized in that: The immersion ultrasonic power of the immersion treatment is 450-470W, the immersion time is 20-30min, and the mass fraction of the sulfuric acid solution is 5%.

5. The shadow blue glaze according to claim 3, characterized in that: The mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%; the mass fraction of the cerium nitrate solution is 4-6%.

6. The shadow blue glaze according to claim 3, characterized in that: The ultrasonic power of the ultrasonic modification treatment is 350-400W, the ultrasonic time is 20-30min, and the mass fraction of the lanthanum chloride solution is 3-5%.

7. A ceramic with a shadow blue glaze, prepared by the method for preparing a ceramic with a shadow blue glaze as described in any one of claims 1 to 2.

Citation Information

Patent Citations

  • Shadowy blue ware porcelain product and production process thereof

    CN108358602A